PENGUKURAN KINERJA PADA MESIN PUNCH HOLE MENGGUNAKAN METODE OVERALL EQUIPMENT EFECTIVENESS (OEE) PADA DI PT.XYZ - Rizky Kurniawan; Rizky Fajar Ramdhani; Akhsani Nur Amalia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to evaluate the effectiveness of the Punch Hole machine at PT. XYZ using the Overall Equipment Effectiveness (OEE) method, identify the factors causing performance losses through the Six Big Losses analysis, and propose improvement strategies. A descriptive quantitative approach was employed using operational data from January to December 2025, including operating time, downtime, production output, and defective products. Data were collected through observation, interviews, and documentation, then analyzed using the OEE indicators (Availability, Performance, and Quality), followed by Six Big Losses and Fishbone Diagram analyses. The results indicate that the OEE value of the Punch Hole machine ranged from 41% to 63%, which is below the world-class standard of 85%. The dominant factors reducing machine effectiveness were Reduced Speed Losses (35%) and Equipment Failure Losses (12%). The Fishbone Diagram revealed that the primary causes originated from machine, method, and material factors. The novelty of this study lies in integrating OEE, Six Big Losses, and Fishbone Diagram analyses to develop a preventive maintenance strategy for improving machine effectiveness and production productivity.